Endoscopic Ultrasound and Pancreas Divisum - Rana, Surinder S; Gonen, Can; Vilmann, Peter (JOP. Journal of the Pancreas, 2012)
Pancreas divisum is the most common congenital anatomic variation of the pancreatic ductal anatomy and in most of the individuals it is asymptomatic. However, in minority of individuals it is presumed to cause recurrent acute pancreatitis and chronic pancreatitis. Endoscopic retrograde cholangiopancreatography is the gold standard for its diagnosis, but is invasive and associated with significant adverse effects. Endoscopic ultrasound (EUS) allows the detailed evaluation of the pancreaticobiliary ductal system without injecting contrast in these ducts. Moreover, it provides detailed images of the parenchyma also. Therefore EUS, both radial and linear, has potential for being a minimally invasive diagnostic modality for pancreas divisum. A number of EUS criteria have been suggested for the diagnosis of pancreas divisum. These criteria have varying sensitivity and specificity and hence there is a need for objective and uniform criteria that have the best diagnostic accuracy. Secretin EUS has a potential for diagnosing minor papilla stenosis and thus help in planning appropriate therapy. EUS guided pancreatic duct interventions can help in draining dorsal duct in symptomatic patients with failed minor papilla cannulation. But these techniques are technically demanding and associated with potential severe complications.